Mental health literacy as a moderator relationship between self-diagnosis and help-seeking behavior in adolescent Posyandu - Aufa, Nisaul; Saniatuzzulfa, Rahmah (Universitas Ahmad Dahlan, 2024)
In the context of rapid societal changes and the digital era, adolescents are increasingly vulnerable to mental health issues, which are often reflected in help-seeking behavior. A significant 34.9% of adolescents exhibit symptoms of mental disorders, yet only 2.6% seek professional help. The establishment of adolescent health posts (Posyandu) serves as a platform for monitoring adolescent health. However, challenges remain due to the low response rates in help-seeking behaviors and limited interest in Posyandu activities. This study aims to examine the relationship between self-diagnosis and help-seeking behavior, moderated by mental health literacy, among adolescents in Posyandu in the city of